2019
DOI: 10.1155/2019/4878912
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supplementation with Some Essential Oils on the Mobility and the Vitality of Human Sperm

Abstract: The objective of this work is to study the improvement effect of some essential oils of sage (Salvia officinalis), oregano (Origanum vulgare), and eucalyptus (eucalyptus globulus) on the physiological parameters characterizing the quality of human sperm (mobility and vitality). We find natural biomolecules to improve sperm quality to increase the chances of success of very low in vitro fertilization (IVF) that stagnate around 20%. Sperm samples were mixed with different concentrations of essential oils. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Our previous work had shown that the in vitro supplementation of the essential oil of oregano during 5 and 10 min of incubation at 37°C under 5% of CO 2 significantly improved the mobility and the vitality of the spermatozoa [3].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Our previous work had shown that the in vitro supplementation of the essential oil of oregano during 5 and 10 min of incubation at 37°C under 5% of CO 2 significantly improved the mobility and the vitality of the spermatozoa [3].…”
Section: Introductionmentioning
confidence: 94%
“…Informed consent was obtained from all patients included before using their sperm in this study. Then, samples were collected after 3 to 4 days of abstinence in sterile and labelled containers [3]. For liquefaction, the samples were stored at 37°C under 5% CO 2 until use.…”
Section: Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations